2017
DOI: 10.1097/jom.0000000000001053
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Work Task-Related Acute Occupational Smoke Exposures on Select Proinflammatory Immune Parameters in Wildland Firefighters

Abstract: Results from this study suggest that intermittent occupational diesel exposures contribute to cross-work-shift changes in host systemic innate inflammation as indicated by elevated interleukin-8 levels and peripheral blood segmented-neutrophils.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 20 publications
2
50
0
Order By: Relevance
“…The subjects did not use respiratory protection during the study. A detailed description of the sample collection methods and gravimetric analyses were reported previously (Adetona AM 2016) In brief, all exposure monitoring instruments were calibrated prior to use, and gravimetric analyses followed the United States Environmental Protection Agency (U.S. EPA) specifications (U.S. Environmental Protection Agency.…”
Section: Methodsmentioning
confidence: 99%
“…The subjects did not use respiratory protection during the study. A detailed description of the sample collection methods and gravimetric analyses were reported previously (Adetona AM 2016) In brief, all exposure monitoring instruments were calibrated prior to use, and gravimetric analyses followed the United States Environmental Protection Agency (U.S. EPA) specifications (U.S. Environmental Protection Agency.…”
Section: Methodsmentioning
confidence: 99%
“…[42] For occupational exposure to combustion particles, both positive and negative studies were identified. [22,50,[80][81][82][83] Taken together, occupational biomonitoring studies report increased blood levels of acute phase response proteins among workers following occupational exposure to particles especially in controlled studies, where the participants serve as their own control. In other studies, including cross-sectional studies, positive correlations between exposure to particles and acute phase response proteins CRP and SAA were found.…”
Section: Biomonitoring Studies Of Occupational Exposure To Particles mentioning
confidence: 99%
“…Detail of the recruitment procedure has been previously reported. 14 Briefly, twelve healthy wildland firefighters (9 males and 3 females with an average age of 33 years) were recruited from US Forest Service-Savannah River Site, SC during January to July 2015. The subjects were briefed face-to-face on the purpose, design, and sample collection procedures of the study.…”
Section: Methodsmentioning
confidence: 99%